Discursive Study of Religion. Reviewing the State of the Art in Finland - Kyyrö Jere (Finnish Society for the Study of Religion, 2025)
This article reviews the state of the art of the discursive study of religion (DSR) in Finland through two recent monographs and an edited volume. These are approached from the point of view of a potential user of the conceptual tools of DSR, as well as a teacher of qualitative methods. The article summarizes the definitions of, variations within, as well as typologies and levels of DSR as they are portrayed in the three books. Finally, attention is paid to some practicalities of doing DSR.